How to approach the island of stability: Reactions using multinucleon transfer or radioactive neutron-rich beams? - Long Zhu (Physics Letters B, 2022)
The multinucleon transfer (MNT) process and radioactive beam induced fusion-evaporation (FE) reactions are the considered routines to explore the island of stability. We make the first direct comparison of the two approaches for producing neutron-rich superheavy nuclei, especially the predicted double magic isotope 298Fl. The radioactive beams 49−59Ca induced hot FE reactions with actinide targets and the MNT reaction 238U + 252Cf are investigated within the framework of the dinuclear system model. Based on the beam intensities proposed by Argonne Tandem Linac Accelerator System, we find that the MNT and FE processes are comparable for producing 298Fl. The influence of the shell structures uncertainties on the production cross section of 298Fl is evaluated. It is found that the shell structures weakly influence the production cross sections of 298Fl around the optimal incident energy, although, the double shell closures could strongly enhance the stability of 298Fl. We also quantitatively estimated the relative proportion of shell effects on cross sections in the transfer stage of the MNT reaction 238U + 252Cf. It is demonstrated that the shell effects on production cross section of 298Fl are mainly from de-excitation process. The general conclusion of this work is that the radioactive beam induced FE reactions show advantages for the excursion toward N=184 from current status.